The Vocalization Systems of Arabic, Hebrew, and Aramaic : Their Phonetic and Phonemic Principles - Morag, Shelomo (Berlin ; Boston : De Gruyter Mouton, 2019)
To celebrate the 270th anniversary of the De Gruyter publishing house, the company is providing permanent open access to 270 selected treasures from the De Gruyter Book Archive. Titles will be made available to anyone, anywhere at any time that might be interested. The DGBA project seeks to digitize the entire backlist of titles published since 1749 to ensure that future generations have digital access to the high-quality primary sources that De Gruyter has published over the centuries.
Frontmatter -- PREFACE -- TABLE OF CONTENTS -- INTRODUCTION -- 1. ARABIC -- 2. HEBREW -- 3. ARAMAIC -- 4. MOTIVATION AND METHODOLOGY IN THE VOCALIZATION SYSTEMS: SOME REFLECTIONS -- 5. TABLES -- 6. BIBLIOGRAPHY
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Okt 2019)
Keywords: 2 -- isacsh